Chronic traumatic encephalopathy: what do parents of youth athletes know about it?. (6th December 2018) - Daugherty, Jill; Sarmiento, Kelly
ABSTRACT: Introduction/Background : Chronic Traumatic Encephalopathy (CTE) is a neurodegenerative disease thought to be caused by repeated head impacts and associated with deficits in cognition. Despite research and media attention, there is little science-based information available for the public. Also unclear is what the public and particularly parents of youth athletes know about CTE. The U.S. Centers for Disease Control and Prevention (CDC) surveyed parents of young athletes to fill this gap. Methods : CDC analysed 12 CTE-related questions that appeared in Porter Novelli Public Service's 2017 SummerStyles opinion survey. Analyses focused on 674 parents of children who play in a youth sports programme. Results : Half of parents had at least one child who plays contact sports. About one-third of respondents reported being somewhat or very familiar with CTE. Most parents (81.7%) have not received educational materials on CTE from a school or sports programme. Healthcare providers were the preferred source of information about CTE (70%), followed by sports coaches (54%). Discussion/Conclusion : This analysis identified information needs related to CTE among parents of young athletes. These findings can be used by health educators to tailor educational materials to meet information needs. Educational materials that emphasize potential prevention strategies and symptom onset may be beneficial.